Korean Hallyu: Parasocial Interaction Study of Teenage K-Popers - Fitri, Dian; Ruwanti, Asti; Cahyani, Firunika Intan (In Trend : International Journal of Trends in Global Psychological Science and Education, 2024)
This research aims to examine teenagers' low awareness of the nature of parasocial interactions and time management skills in consuming K-Pop content and social media, and how this can disrupt the balance of teenagers' daily lives. The method used in this research is a descriptive quantitative method, which is known as a traditional method because it has been used for a long time and is common in research. The population of this research is teenage K-Pop fans who actively use social media, using non-probability sampling techniques. The characteristics of the research subjects are teenagers aged between 12 and 22 years who are K-Pop fans and social media users. Data was collected through a questionnaire using a Likert scale to measure parasocial interactions and social media consumption patterns. The results showed that subjects with high social media use had a high level of parasocial interaction. Activities such as scrolling timelines and feeds, enjoying content for fun, and learning Korean from idol posts have a medium level of parasocial interaction. In contrast, activities such as searching for information about idols, watching music videos, voting for idols, and watching concerts and idol content show high to very high levels of parasocial interaction. This research reveals that excessive social media consumption in the K-Pop context can lead to intense parasocial interactions, which have the potential to disrupt the balance of teenagers' daily lives. It is hoped that these findings can become the basis for efforts to increase adolescent awareness regarding time management and healthy social media consumption.